NUTRITIVE VALUE OF ENSILED CASSAVA (Manihot esculentus, Crantz) TOPS AND GUINEA GRASS (Panicum maximum) FOR THE WEST AFRICAN DWARF SHEEP (2013)
Cassava Tops (CT), a crop residue, is available all year round but its potential utilisation is low. The Crude Protein (CP) and other nutrients in CT could be beneficial to ruminant livestock. Information on CT preservation and nutritive value is scanty. Therefore, the nutritive value of ensiled CT with Guinea grass to the West African Dwarf (WAD) Sheep was investigated. Cassava tops and Guinea Grass (GG) of eight weeks re-growth with four energy additives were combined in ratio 3:6:1 into five treatments: 1 (CT + GG + cassava chips), 2 (CT + GG + Sorghum), 3 (CT + GG+ millet grains), 4 (CT + GG + sugar ) and 5 (CT + GG + no additive). After 42 days of ensiling, silage characteristics, chemical composition: Dry Matter (DM), CP, ash, Neutral Detergent Fibre (NDF), and Acid Detergent Fibre (ADF) and acceptability by 8 WADS using Coefficient of Preference (CoP) procedure were determined. In a completely randomised design, 25 WAD sheep were fed with the five silages for 135 days to evaluate Dry Matter Intake (DMI), Daily Weight Gain (DWG), Dry Matter Digestibility (DMD), Packed Cell Volume (PCV) and Serum Total Protein (STP) using standard procedures. Carcass characteristics: dressing percentage, prima cuts, internal organs and external offals were measured. Further, effect of Length of Storage (LS) (72, 102, 132, 162, 192 and 222 days) on silage characteristics, chemical composition and the nutritive value of silage were assessed using in vitro fermentation technique to obtain potential extent of gas production (a+b), potential gas production (b), rate of gas production (c), Organic Matter Digestibility (OMD), Metabolisable Energy (ME) and Short Chain Fatty Acids (SCFA). Data were analysed using descriptive statistics and ANOVA at p=0.05. The colour of the silages was olive green with pleasant odour, firm texture and pH range of 4.3 to 5.1. Dry Matter (27.1-28.8%), CP (21.8-24.9%), ash (7.6-9.4%), NDF (68.8-71.7%) and ADF (40.6-48.1%) of the silages differed significantly among treatments. Silages with cassava chips (1.19), sorghum (1.11) and millet (1.09) additives were more acceptable as CoP was above unity. The DMI (472.6-530.0 g/d) and DMD (75.8-84.7%) differed significantly while DWG was similar among treatments. The PCV and STP varied significantly and ranged from 27.0 to 33.7% and 6.08 to 8.20g/dl respectively. Dressing percentages ranging from 50.8 to 53.8% were significantly different. The Prima cuts (loin; 12.0-14.9%, rack; 15.6-18.9%, neck; 10.3-12.1%), liver (7.4-8.1%) and skin (1.5-1.8%) were significantly different. Relative weight of leg, shoulder, head, feet and other organs were not significantly different. The DM (28.0-29.6%), CP (23.7-27.1%), ash (8.8-10.0%), NDF (57.9-71.5%), and ADF (44.1-49.8%) were all significantly influenced by LS. Gas production (17.67-30.07 ml/96 hours), b (16.20-28.00ml), ME (6.09-7.68 MJ/kg DM), OMD (62.9-73.2%) and SCFA (0.48-0.78 mmol) were also significantly influenced by LS.Cassava tops and Guinea grass ensiled with all additives used, had good silage properties and enhanced nutritive value. Preservation of silages was possible for seven months without loss of nutrients